Religion and political theory secularism, accommodation and the new challenges of religious diversity - Seglow, Jonathan 1968-; Shorten, Andrew 1979- (Rowman & Littlefield International, 2019)
Featuring the work of both established and up-and-coming scholars, this collection takes stock of the recent turn towards religion in political theory, identifies some of the major unresolved challenges and issues, and suggests new avenues for theoretical inquiry
Keywords: Religion; Säkularismus; Politische Theorie; Religion and politics; Aufsatzsammlung